Organizations as Open Systems That Need Purpose and Integrated Thinking. Issue 150 (March 2017) - Hurth, Victoria
Abstract : The world is changing more rapidly than ever. Here, Victoria Hurth, Associate Professor in Marketing and Business Sustainability at Plymouth University UK, discusses the extent to which the role of the organization has to change within it.